Tugu Soekarno Palangka Raya: Pertentangan Antara Identitas Indonesia - Tarupay, Heri Kusuma (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Inaugural visit of President Soekarno to Palangka Raya on July 17, 1957, marked by the establishment of Tugu Soekarno, carries two meanings. The first meanings, from the perspective of the Indonesian government in Jakarta, is that this visit symbolizes ther formalization of Central Kalimantan Province as one of the provinces in the unitary state of the Republic of Indonesia. The second meaning, from Dayak community’s perspective, is that this visit is seen as a recognition of Dayak identity. These two meanings have been continuously debated over time since President Soekarno first visit, and Tugu Soekarno has become a symbol of this two-way communication. Using observation and document analysis methods, this writing examines the symbolic communication of Tugu Soekarno in Palangka Raya, which continues to symbolize the tug of war between Indonesia and the Dayak community